2021
DOI: 10.1016/j.tsf.2021.138538
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermal annealing on the optoelectronic properties of Cu-Fe-O thin films deposited by reactive magnetron co-sputtering

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Based on our previous assumption, on which oxygen content would be affected by the temperature deposition, a progressive decrease of the refractive index would then be expected with the deposition temperature elevation. In previous study dealing with the annealing conditions of sputtered CuFeO2 films [35], it was observed that a slight enhancement of the reductive conditions (increase of annealing temperature in primary vacuum) leads to the formation of Cu2O and Fe2O3 phases from rhombohedral delafossite phase, while with even more reductive conditions (same temperature range combined with secondary vacuum) only Cu and Fe3O4 phases crystallize. Refractive indices of Cu2O and Fe2O3 are 2.6 to 2.27 and 2.78 to 2.66 in the infrared range (1000 to 2600 nm, respectively) [36], and the refractive indices of metallic Cu included from 0.46 to 1.09 and of the spinel Fe3O4 are included from 2.13 to 2.85 at 1000 to 2600 nm, respectively.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Based on our previous assumption, on which oxygen content would be affected by the temperature deposition, a progressive decrease of the refractive index would then be expected with the deposition temperature elevation. In previous study dealing with the annealing conditions of sputtered CuFeO2 films [35], it was observed that a slight enhancement of the reductive conditions (increase of annealing temperature in primary vacuum) leads to the formation of Cu2O and Fe2O3 phases from rhombohedral delafossite phase, while with even more reductive conditions (same temperature range combined with secondary vacuum) only Cu and Fe3O4 phases crystallize. Refractive indices of Cu2O and Fe2O3 are 2.6 to 2.27 and 2.78 to 2.66 in the infrared range (1000 to 2600 nm, respectively) [36], and the refractive indices of metallic Cu included from 0.46 to 1.09 and of the spinel Fe3O4 are included from 2.13 to 2.85 at 1000 to 2600 nm, respectively.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Electron scattering impacts the transmission of light while operating at elevated powers and temperatures as a result of larger crystallite sizes and rougher surfaces. The film thickness was determined by using transmission data through the Swanepoel envelope technique [59]. It was noted that when the level of deposition power increased from 200 to 260 W, the film thickness also increased from 1079 to 1198 nm.…”
Section: Cosɵ = Acosɵ`mentioning
confidence: 99%
“…The value of refractive index 'n' for the sputtering power of 200 to 260 W is in the range of 1.49 to 1.51, while for deposition temperature from 50 to 200 °C, it varies from 1.50 to 1.52, which is mentioned in Table 3. The film thickness was determined by using transmission data through the Swanepoel envelope technique [59]. It was noted that when the level of deposition power increased from 200 to 260 W, the film thickness also increased from 1079 to 1198 nm.…”
Section: Cosɵ = Acosɵ`mentioning
confidence: 99%
See 1 more Smart Citation
“…Spinel oxides provide tunability of their properties through alterations to the synthesis conditions. Magalhães et al studied the impact of heat treatment on the catalytic properties of iron cobaltite (FeCo 2 O 4 ) nanoparticles prepared via coprecipitation . The XPS results revealed a higher cobalt content on the surface of nonheated samples compared to those treated to 900 °C, which was attributed to the enhanced catalytic activity in the unannealed samples.…”
Section: Introductionmentioning
confidence: 99%